2007
DOI: 10.1038/ismej.2007.51
|View full text |Cite
|
Sign up to set email alerts
|

Fungal communities from methane hydrate-bearing deep-sea marine sediments in South China Sea

Abstract: To elucidate fungal diversity in methane hydrate-bearing deep-sea marine sediments in the South China Sea, internal transcribed spacer (ITS) regions of rRNA genes from five different sediment DNA samples were amplified and phylogenetically analyzed. Total five ITS libraries were constructed and 413 clones selected randomly were grouped into 24 restriction patterns by Amplified Ribosomal DNA Restriction Analysis (ARDRA). ITS sequences of 44 representative clones were determined and compared with the GenBank dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 37 publications
7
120
2
Order By: Relevance
“…Fungi isolated from deep seas were first reported nearly 50 years ago (Roth et al 1964), then a great number of fungi including some novel species have been published by both conventional culture-dependent (Raghukumar et al 2004; Gadanho and Sampaio 2005; Damare et al 2006; Nagahama et al 2006; Le Calvez et al 2009; Singh et al 2010) and culture-independent methods (Lai et al 2007; Le Calvez et al 2009; Nagano et al 2010). Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods.…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Fungi isolated from deep seas were first reported nearly 50 years ago (Roth et al 1964), then a great number of fungi including some novel species have been published by both conventional culture-dependent (Raghukumar et al 2004; Gadanho and Sampaio 2005; Damare et al 2006; Nagahama et al 2006; Le Calvez et al 2009; Singh et al 2010) and culture-independent methods (Lai et al 2007; Le Calvez et al 2009; Nagano et al 2010). Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods.…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Other OTUs (otu3, 7 and 11) belonging to the Ascomyta phylum were also present in the center and top, but only otu11 could be precisely assigned (97% similarity) to sequences from spring water (Oliveira et al, 2013). In the Canyon after 210 days, the most abundant fungal OTU was an Ascomyta that was similar to sequences found in the sea and mangrove sediments with 100% similarity, and another OTU that was 99% similar to a sequence from methane hydrate-bearing deep-sea marine sediments (Lai et al, 2007).…”
Section: Wood Fall Microbial Community Dynamics D Kalenitchenko Et Almentioning
confidence: 86%
“…Strains belonging to the genera Rhodosporidium, Rhodotorula, and Candida have been frequently found in deep-sea environments, using culture-independent methods. On the contrary, species of the genera Cryptococcus, Pichia, and Trichosporon seem to be detected more frequently using culture-independent methods than by using culture-dependent methods (Bass et al 2007;Lai et al 2007;Nagano et al 2010;Singh et al 2010). The basidiomycetous yeast Cryptococcus curvatus was found to be the dominant eukaryotic microorganisms in oxygen-depleted sediments from deep-sea methane seeps at the Kuroshima Knoll (Takishita et al 2006).…”
Section: Yeast Diversity In Deep-sea Environmentsmentioning
confidence: 92%
“…The advantages of using molecular methods are mainly the requirement of only a small amount of samples and the detection of difficult-to-culture or unculturable species, including rare species. Yeast species which have not been reported by culture-dependent methods have been detected by culture-independent methods from deep-sea environments (Bass et al 2007;Lai et al 2007;Le Calvez et al 2009;Nagano et al 2010;Singh et al 2010Singh et al , 2011Nagahama et al 2011). Strains belonging to the genera Rhodosporidium, Rhodotorula, and Candida have been frequently found in deep-sea environments, using culture-independent methods.…”
Section: Yeast Diversity In Deep-sea Environmentsmentioning
confidence: 98%
See 1 more Smart Citation